Global research trends on gastrointestinal cancer and mental health (2004–2024): a bibliographic study - Han, Wenjin; Wang, Tianmeng; He, Zhiqiang; Wang, Caihua; Hui, Zhaozhao; Lei, Shuangyan; Hao, Nan; Li, Ning; Wang, Xiaoqin (Frontiers in Medicine, 2025)
BackgroundGastrointestinal (GI) cancers impose a significant burden on global public health. Patients often experience mental health challenges due to physical changes and treatment-related symptoms, which can worsen their condition or delay recovery. Although research is mounting in this field, visual bibliometric analysis has not yet been conducted. This study aims to reveal the research hotspots and frontiers in this field using bibliometrics to guide future research.MethodsThe publications on GI cancer and mental health were retrieved in the Web of Science Core Collection from 2004 to 2024. VOS Viewer and CiteSpace, as commonly used bibliometric analysis tools, were employed to visualize the network structure of bibliometric data and uncover the evolving trends in scientific research fields. VOS Viewer was used to identify keyword co-occurrences, while CiteSpace was utilized to generate network visualizations, produce dual-map overlays of journals, and perform burst keyword analysis.ResultsA total of 1,118 publications were included for analysis. China had the highest number of publications in this field (341, 30.5%), while the United States held a central position (centrality = 0.48). The most productive author and institution were Floortje Mols and Tilburg University, respectively. Keyword analysis highlighted that “quality of life” (QoL) is a prominent research topic in the field, while “complications,” “cancer-related fatigue,” (CRF) “chronic stress,” and “epidemiology” have been identified as key areas for future research.ConclusionResearch interest in this field continues to grow. The research direction is mainly focused on personalized mental health interventions to improve QoL, as well as preoperative mental healthcare and ongoing care through internet-based multidisciplinary collaboration to reduce postoperative complications. More detailed clinical symptom assessment is needed to distinguish between CRF and mental health issues and to provide targeted intervention measures in the future. The mechanism of mental health effects on the occurrence and development of GI cancer will be a frontier.